The Begum’s Zubaan : the construct of an emotional community through the language and representation of female emotion - Sarah Farheenshah Begum Mohd Sultan (2017)
There exists a dichotomy between religion and social function behind the practice of the purdah evident in the matriarch rule of Nawab Sultan Jahan Begum. Her adaptation of the idealized values of Muslim women through her rule is apparent in her written accounts both personal and published which document her experiences in donning the veil as well as the opinions she forged and combined in relation to her position in society in both gender and status. This thesis emphasizes on how Begum’s status as a woman of courtly rule allowed for the formation of an emotional community through her articulation of femininity and women’s roles in relation to the practice of the purdah. This relates to Begum’s construction of femininity and womanhood through a language of emotion evident in her writing. Class will be explored in terms of its interactions with gender in the case of Bhopal, as an integral factor in achieving and propagating societal freedom. There existed a varying amount of mobility attached to the social statuses of middle-class and lower-class women which was both a unifying and divisive factor within the female community.